Development and Globalization - United Nations Conference on Trade; Development (United Nations, 2022)
The purpose of this statistical report is to promote UNCTAD statistics and UNCTAD's engagement with Agenda 2030. Small island developing States (SIDS) face an uphill battle as they strive to recover from the impact of the COVID-19 crisis amid vulnerabilities worsened by the pandemic. The 2021 edition of UNCTAD’s Development and Globalization: Facts and Figures report, highlights the numerous strengths and challenges facing these economically vulnerable countries.